2000
DOI: 10.1246/cl.2000.806
|View full text |Cite
|
Sign up to set email alerts
|

Rotaxanes Functionalized by Chirality: Novel Rotaxanes Consisting of Binaphthol-Based Chiral Crown Ether

Abstract: A chiral crown ether 1 was synthesized from (R)-1,1′-bi-2-naphthol. Chiral rotaxanes were prepared by end-capping of pseudorotaxanes consisting of 1 and secondary ammonium salts. An ammonium salt bearing terminal anthracene group gave stable pseudorotaxane. Chiral induction was observed during end-capping by radical conjugate addition of a bulky thiol to the pseudorotaxane bearing methacrylate group at the terminus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…13 Chiral rotaxanes may be chiral from inclusion of classical stereogenic elements or by virtue of being mechanically planar chiral. Since then, several examples followed, [14][15][16][17][18][19][20][21][22][23][24][25] in which the mechanically interlocked structure was used to induce directionality in polymers, [26][27][28] for sensing, [29][30][31] and to act as an enantioselective catalyst. 32 Today, sophisticated synthetic protocols allow an efficient enantioselective synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…13 Chiral rotaxanes may be chiral from inclusion of classical stereogenic elements or by virtue of being mechanically planar chiral. Since then, several examples followed, [14][15][16][17][18][19][20][21][22][23][24][25] in which the mechanically interlocked structure was used to induce directionality in polymers, [26][27][28] for sensing, [29][30][31] and to act as an enantioselective catalyst. 32 Today, sophisticated synthetic protocols allow an efficient enantioselective synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the NOESY spectra of the pseudorotaxane 1…2a in d-chloroform as shown in Fig. 5(a), clear correlations were observed between the benzylic phenyl protons (f) of the macrocycle 1 and proton (2) of phenanthroline (2a), benzylic phenyl protons (g) of the macrocycle 1 and protons (4, 5) of phenanthroline (2a), benzylic phenyl protons (f) of the macrocycle 1 and protons (2) of phenanthroline (2a), and the oxyethylene protons (h, i, j) of the macrocycle 1 and protons (4,5) of phenanthroline (2a), confirming that phenanthroline (2a) was incorporated within the macrocycle 1 in d-chloroform. When 3 drops of trifluoroacetic acid as an acid stimulus were added into the pseudorotaxane 1…2a in d-chloroform, no distinct cross peaks were observed between the protons (f, g, h, i, j) of the macrocycle 1 and the protons (2,4,5) of phenanthroline (2a) in the NOESY spectra as shown in Fig.…”
Section: Acid-base Controlled Switching Studiesmentioning
confidence: 92%
“…1 Moreover, intense recent research has been focused on technological applications of exploiting rotaxanes and catenanes as molecular sensors 2,3 and catalysts. 4 For example, Hiratani et al 3 reported that three-dimensional cavities between axles and wheels in the rotaxanes are capable of binding particular alkali metal cations and one enantiomer of an aminoalcohol selectively.…”
Section: Introductionmentioning
confidence: 99%
“…17a ). 53 More recently, Takata and co-workers reported chiral rotaxanes ( R )- 41 and observed diastereoselective N -oxidation when rotaxanes ( R )- 41 were treated with dimethyldioxirane ( Fig. 17b ).…”
Section: Chiral Covalent Stereogenic Unitsmentioning
confidence: 97%